Implementasi Metode Demonstrasi Berbantuan Google Classroom Untuk Meningkatkan Minat Belajar Mahasiswa Kelas A Prodi PGSD - Ni Nyoman Kurnia Wati (STAHN Mpu Kuturan Singaraja, 2020)
This study aims to increase the interest in learning of class A students in semester 5 of the 2019/2020 academic year at the PGSD study program at STAHN Mpu Kuturan Singaraja through the implementation of the Google Classroom assisted demonstration method. The research subjects of class A semester 5 students were 20 people. While the object of this research is student interest in learning by implementing the Google Classroom assisted demonstration method. Data on the results of learning implementation are collected by observation method. The data obtained were analyzed using descriptive statistical analysis. Based on the results of the data analysis, it can be concluded that the implementation of the Google Classroom assisted demonstration method can increase the interest in learning of Class A students in semester 5 of 2019/2020 academic year at the PGSD study program at STAHN Mpu Kuturan Singaraja. This result is evident from the increase in the average of the first cycle of 14.75 to 18.52 in the second cycle. Classical completeness of students also increased from 65% in the first cycle to 95% in the second cycle. Keywords: demonstration method, Google Classroom, interest in learning